Implementation of Alcohol-Related Care in 3 Veterans Health Administration Hepatology Clinics: A Mixed-Methods Summative Evaluation - Emily C. Williams; Madeline C. Frost; Olivia V. Fletcher; Carol E. Achtmeyer; Jessica A. Chen; Rachel L. Bachrach; E. Jennifer Edelman; Bryan J. Weiner; George N. Ioannou; Judith I. Tsui (Substance Use & Addiction Journal, 2026)
Background: Hepatology specialty clinics present a unique opportunity to provide alcohol-related care (brief counseling, treatment referral, medications for alcohol use disorder [MAUD]). We used practice facilitation to implement alcohol-related care in 3 distinct Veterans Health Administration hepatology clinics in the western U.S. and conducted a mixed-methods summative evaluation assessing documented alcohol-related care (adoption) and patient experiences (acceptability/fidelity). Methods: Three sources of data were triangulated. Electronic health record (EHR) data extracted for patients receiving care at the 3 clinics pre-, during, and post-implementation measured patient characteristics and trends in documented alcohol-related care (adoption). Structured chart reviews for a random sample of 137 patients with documented unhealthy alcohol use assessed documentation of 3 additional adoption measures: (1) alcohol-related discussions, (2) discussion of/referral to treatment, and (3) discussion/receipt of MAUD. Qualitative interviews with 12 patients (4/clinic) with documented alcohol-related discussions during the implementation/post-period were conducted to assess patients’ perspectives (acceptability/fidelity). Results: Five thousand four hundred three unique patients were seen during the study; 2566 at Site 1, 2428 at Site 2, and 409 at Site 3. EHR data showed dynamic but little overall change in alcohol use or alcohol-related care over time. In chart reviews during pre-implementation, 74% had documented alcohol discussions, 23% of those with alcohol discussions had discussion of/referral to treatment, and 15% had discussion/receipt of MAUD. During/post-implementation, 75% had alcohol discussions, 59% of those with alcohol discussions had discussion of/referral to treatment, and 25% had discussion/receipt of MAUD. Interview participants generally remembered and were satisfied with alcohol-related discussions. Patients appreciated when clinicians described how liver damage can reverse with abstinence and expressed confidence in their ability to abstain. Conclusions: Practice facilitation may have supported adoption of alcohol-related care in hepatology clinics, which patients generally appreciated. Clinicians in hepatology specialty clinics should encourage honesty, emphasize the benefits of abstinence, and provide patient-centered messaging.